Elements of Negligence by Regional Governments in Designating Cultural Heritage as Cultural Heritage - Herri Suryadi Samosir; Wahyu Prawesthi; Sri Astutik (Eduvest - Journal of Universal Studies, 2026)
Cultural heritage refers to objects, buildings, structures, sites, and areas — both on land and in water — that have been designated as Cultural Heritage, are material in nature, and need to be preserved. The determination of Cultural Heritage carries significant meaning within the Indonesian legal system, as it represents an active legal measure taken by the state to protect cultural heritage that is important for history, science, education, religion, and culture. This research aims to analyse the elements of negligence by regional governments in designating cultural heritage as Cultural Heritage, and to identify the legal implications and losses caused by such negligence. This research uses a normative juridical approach, examining legal norms, regulations, and doctrines, as well as a case analysis of Medan District Court Decision Number 756/Pdt.G/2020/PN Mdn concerning Medan Merdeka Square. The determination of Cultural Heritage is the obligation of the regional government (Regent/Mayor) after receiving recommendations from the Cultural Heritage Expert Team. Without an official determination, a cultural heritage object is in a legally vulnerable condition, as it lacks a clear protection status, creating opportunities for theft, destruction, transfer, conversion, demolition, or use contrary to its historical value and the public interest. Government negligence in designation constitutes an unlawful act and violates constitutional obligations and the General Principles of Good Governance, particularly with regard to legal certainty and the protection of the public interest.